Carbohydrate concentration in 'BRS Rubimel' peach trees during the annual cycle - Gonçalves, Bruno Henrique Leite [UNESP]; Leonel, Sarita [UNESP]; Tecchio, Marco Antônio [UNESP]; Ferraz, Rafael Augusto [UNESP]; Souza, Jackson Mirellys Azevedo [UNESP]; Arruda, Lucas Lencioni [UNESP] (Sciencedomain International, 2015)
The carbohydrate storage is necessary to support the plant growth in periods of stress, during the dormancy, in the beginning of the vegetative development and during the fruiting time. In this context, this work intended to evaluate the carbohydrate concentrations of the peach (Prunus persica (L.) Batsch) tree ‘BRS Rubimel’, cultivated under subtropical conditions. The experiment was performed at the experimental farm Lageado, of the Faculty of Agricultural Sciences of UNESP at Botucatu/SP. The evaluated peach trees were two years old and were cultivated in the spacing of 6.0 x 4.0 m. The adopted experimental delineation was in randomized blocks, making use of four plants per parcel with four repetitions. The treatments corresponded to the period of the collection of leaves and branches, during the annual cycle, corresponding to January to May and July to December 2012. The sample collection of the roots was performed in January, April, August, November and December 2012. Four fruits per plant were collected. The concentration of starch in the roots of the peach tree were superior to the ones from the branches, from August to December. The carbohydrate with the higher storage level in the peach tree ‘BRS Rubimel’ was starch.
Keywords: Prunus persica L. Bastch; Photo-assimilated compounds; Sugars